A fuzzy-based approach to understanding barriers in implementing VR and AR for construction safety training - Calik, Idil; Koc, Kerim; Mohandes, Saeed Reza; Ali, Ali Hassan; Ekmekcioglu, Omer; Kidd, Callum (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThis study aims to examine the interactions among the barriers impeding the use of virtual reality (VR) and augmented reality (AR) technologies for construction safety training and to investigate how these barriers affect the general safety management system. The study uses a hybrid fuzzy-based algorithm to offer a thorough and organised knowledge of these dynamics, thereby attaining this goal.Design/methodology/approachThis study employs a systematic literature review (SLR) approach combined with the Fuzzy Decision-Making Trial and Evaluation Laboratory (FDEMATEL) and Fuzzy Technique for Order of Preference by Similarity to Ideal Solution technique (FTOPSIS) to unravel the related relationships among the barriers and rank the components of the safety management system in terms of their importance levels.FindingsUsing the data collected from the experts in Hong Kong construction sector, the following observations were noted: (1) five barriers and seventeen sub-barriers were identified through an SLR, (2) Using the FDEMATEL technique, cost of implementation, adaptability, require-ments, standardization and compatibility were seen to be the most influential barriers within the corresponding clusters and (3) based on the employment of FTOPSIS technique, safety risk management was the most important component of safety management system in enhancing the adoption and effectiveness of VR/AR technologies for safety training in the construction industry.Practical implicationsFrom the findings derived from this research, stakeholders can develop targeted strategies to overcome challenges to the widespread adoption of immersive technologies, which is not only vital for enhancing worker safety but also for fostering innovation, improving efficiency and supporting the industry's digital transformation.Originality/valueThough some studies have focused on the examination of the barriers impeding the adoption of VR and AR technologies for construction safety training, the current body of literature lacks a thorough understanding of the interrelationships existing among these barriers. Moreover, the relationships between the barriers and the safety management system have not yet been touched on in the literature. Thus, this study fills these critical gaps by employing a hybrid fuzzy-based algorithm.
Keywords: Virtual reality; Augmented reality; Construction safety; Safety training; Fuzzy sets; Multi-criteria decision-making methods; PERFORMANCE EVALUATION; SUPPLIER SELECTION; REVERSE LOGISTICS; DECISION-MAKING; VIRTUAL-REALITY; TOPSIS METHOD; DEMATEL; MANAGEMENT; Construction & Building Technology; Science & Technology - Other Topics; Engineering